Integrating health humanities, social science, and clinical care : a guide to self-discovery, compassion, and well-being - Anna-leila Williams (Oxon : Routledge, 2019)
The health humanities are widely understood as a way to cultivate perspective, compassion, empathy, professional identity, and self-reflection among health professional students. This innovative book links humanities themes, social science domains, and clinical practice to invite self-discovery and recognition of universal human experiences. "Integrating Health Humanities, Social Science, and Clinical Care" introduces critical topics that rarely receive sufficient attention in health professions education, such as cultivating resilience, witnessing suffering, overcoming unconscious bias, working with uncertainty, understanding professional and personal roles, and recognizing interdependence.--[page i]
Keywords: Caregivers education; Public health Psychological aspects; Education, Medical; Compassion